Spatial structure changes inside post-communist capital city of Bucharest - Gabriel Simion; Constantin Nistor (Human Geographies: Journal of Studies and Research in Human Geography, 2012)
The paper focusses on the analyses of the recent development concerning post-socialist urban transformation of Bucharest, the Romanian country capital. The paper describes the spatial typology of metropolitan landscapes, and underlines the changes occurred inside the residential, commercial, services and industrial areas. The most noticeable occurrence is the urban sprawl and multiplication of the buildings and implicitly the diminishing of the agricultural area., It has been confirmed, at least theoretically, that spatial development of the largest cities determined a continuous decreasing of agriculture in the metropolitan area, landowners preferring selling or seeking to sell their land. The paper is empirically trying to argue the fact that post-socialist development of the land market in Bucharest metropolitan area determined a decline of agriculture in the city’s proximity. It is also showing that at increasing distance from the Bucharest city agriculture still has its importance as subsistence activity – in the south-eastern part, or as market oriented – in the south-western part or in the northern border.